Molecular and cytogenetic confirmation of the hybrid origin of Jacobaea ×mirabilis (Asteraceae, Senecioneae), with nomenclatural notes on this name - Mas De Xaxars, Gemma; Fridlender, Alain; Garnatje, Teresa; Vallès, Joan (Phytotaxa, 2015)
Jacobaea ×mirabilis is a hybrid taxon, formerly included in the genus Senecio, originating from J. adonidifolia and J. leucophylla as progenitors. It inhabits a few French mountain locations in the Pyrenees and in the Massif Central. In this paper, we characterize the hybrid and its parental taxa using molecular phylogenetic and cytogenetic (genome size) methods. These data are useful to confirm the hybrid status of the studied taxon. Additionally, we clarify nomenclatural issues connected with this species and fulfil the conditions for valid publication of its name in Jacobaea. The name of this hybrid is also lectotypified.